Tell Me What You Do, I’ll Tell You Who You Are: Predicting Offender-Victim Relationships in Sexual Homicide - Kim, Anny (Victims & offenders, 2025)
This study fills a gap in the existing literature by differentiating between sexual homicides committed by strangers and those by acquaintances. Utilizing data from the Sexual Homicide International Database, which encompasses 772 cases from France and Canada, the research focuses on using victimological and crime scene characteristics to predict the victim-offender relationship in sexual homicides. Employing a comprehensive methodological approach, the study uses bivariate analysis, sequential binary logistic regression, and an artificial neural network (ANN) model. These methods help in examining the correlations and predictive values of various factors in determining the nature of the victim-offender relationship. The findings highlight significant differences in the modus operandi of stranger and acquaintance offenders. Stranger offenders are more likely to exhibit violent, premeditated actions involving weapons, while acquaintance offenders tend to use verbal aggression, exploiting their existing relationship with the victim. Theoretically, results provide empirical insights into the dynamics of sexual homicides, expanding the understanding of offender behavior and crime scene analysis. Practically, it offers valuable guidance for law enforcement in criminal investigations and resource allocation.